STRUKTUR KOMUNITAS ARTHROPODA PADA EKOSISTEM CABAI TANPA PERLAKUAN INSEKTISIDA - Nurkhasanah, Nurkhasanah (MEDIA LITBANG SULTENG, 2011)
Community Structure Arthropods in chilli ecosytem undtreated insectisides. were analysed using tree methods. The methods were sweep net, direct observation for crown arthropods, pitfall trap for soil surface arthropods. The arthropods collected were the examined in the laboratory. The orders and families were identified and classified on the bassis of the guilds. The analysesÂ  showed that the 26 families of 8 orders of arthropods with the total 1942 individuals on chilli crown and 25 families of 11 orders with total 593. As many as three guilds of arthropods were obtained from the structure analyses : phytophags, natural enemies of Arthropods, and others.